Archaeological Analysis of the Newly Discovered Tomb with a Relief of a Couple at the Funerary Area of Porta Sarno in Pompeii - Llorenç Alapont; Rachele Cava; Joaquin Alfonso Llorens; Juan José Ruiz Lopez; Ana Miguélez González; Pilar Mas Hurtuna; Tomas Hurtado Mullor; Victor Revilla; Antoni Puig Palerm; Silvia Alfayé Vila; Altea Gadea Matamoros; Esther Alba Pagan; et al. (Heritage)
In July 2024, the “Investigating the Archaeology of Death in Pompeii Research Project” carried out a scientific and methodical excavation of the areas outside two of the gates to the city of Pompeii. One of them is the funerary area of Porta Nola (next to the tomb of Obellio Firmo) and the other is outside Porta Sarno area (east of the tomb of Marcus Venerius Secundius). The investigated funerary area to the east of Porta Sarno corresponds with the area excavated in 1998 for the construction of the double Circumvesuviana rails. The 1998 excavations recorded the presence of more than 50 cremation burial sites, marked by stelae (columelle) and a monument with an arch, which are delineated by a boundary wall. The tombs were initially dated to the Late Republican period. In order to carry out comprehensive studies of the funerary area uncovered in 1998, a four metre by four metre trench was stratigraphically excavated. This investigation allowed mapping of the area and the carrying out of archaeological analysis and bioarchaeological studies in order to answer the questions that guided our archaeological research, such as whether the funerary area was abandoned and, if so, when? What was the chronological succession, monumentality, and prestige of this funerary space? Was it a single family and private funerary enclosure, or was it an open public space? How were this funerary area and the spaces destined to preserve the memory of the deceased managed? How were the funerary and mortuary rituals and gestures articulated and what did they consist of? Our methodical excavation discovered a monumental tomb which allows us to answer many of the questions raised by our research. This extraordinary monument consists of a wide wall with several niches containing the cremated remains of the deceased built into its structure and which is crowned by a relief of a young couple. The symbolism of the carved accessories of the wife may identify her as a priestess of Ceres. Additionally, the quality of the carving in the sculptures and their archaic characteristics suggest a Republic period dating, which is uncommon in southern Italy.